THEORETICAL FINDING THROUGH MOLECULAR DYNAMICS OF NOVEL PIPERAZINE SULFONYL AMINE BASED NMDA-NR2B RECEPTOR ANTAGONIST (Journal of Pharmaceutical Negative Results, 2023)
Utilizing molecular modelling approaches, a novel family of antagonists of the N-Methyl-D-Aspartate (NMDA) receptor subunit NR2B has been designed. In this study, we performed molecular dynamics (MD) simulations of protein–ligand complexes and determined how well MD simulations correlated the previously reported docking result. Our results suggest that appropriate candidate poses can be chosen from the many docking poses by using MD simulations with implicit solvents. The 25ns simulation suggests that the protein-ligand complexes are stable throughout the time scale. According to the MM/PBSA calculation the most stable Protein-ligand complexes in terms of binding free energies were found in cases with SE-C-13, SE-B-2, and SE-A-8. The designed compound will be subjected to synthetic accessibility analyses. Our results could provide theoretical guidance for the future development of new NMDA-NR2B Receptor Antagonist against Alzheimer.